Comprehensive care : meanings for teachers and nursing students - Rangel, Rosiane Filipin (2017)
Objective : to understand the meaning of comprehensive care in the view of teachers and nursing students. Methods : qualitative research conducted with seven teachers and six students of the nursing course of a higher education institution. Data were collected using the Focal Group technique and subjected to thematic content analysis . The comprehensive care construct was used for this article as based on authors who talk with ownership of the theme. Results: the students perceive the comprehensive care as the subjective interaction with others respecting human uniqueness through a gradual construction in order to meet the apparent and non-apparent needs. Conclusion: teachers and students reported that comprehensive care depends on a network of actions and needs to be instigated since academic education.